2025.6.9 - Cameron, John E. (Northwest Missouri State University, 2026)
Glass-plate negative photograph of a group of men and women, sign in the background reads "Chautauqua Aug 28 Sept 6 Oshkosh." This image is very damaged, only a small portion is visible.